2016
DOI: 10.1002/ange.201603556
|View full text |Cite
|
Sign up to set email alerts
|

Highly Tunable Selectivity for Syngas‐Derived Alkenes over Zinc and Sodium‐Modulated Fe5C2 Catalyst

Abstract: Zn‐ and Na‐modulated Fe catalysts were fabricated by a simple coprecipitation/washing method. Zn greatly changed the size of iron species, serving as the structural promoter, while the existence of Na on the surface of the Fe catalyst alters the electronic structure, making the catalyst very active for CO activation. Most importantly, the electronic structure of the catalyst surface suppresses the hydrogenation of double bonds and promotes desorption of products, which renders the catalyst unexpectedly reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 47 publications
(14 reference statements)
0
8
0
1
Order By: Relevance
“…In addition to alkali metals, the addition of secondary metal could also enhance the production of long-chain hydrocarbons. For instance, cuprum and zinc are commonly used promoters as well, favorable for the reduction of Fe 2 O 3 and the adsorption of CO 2 , which could increase the selectivity for C 5 + hydrocarbons and decrease CH 4 selectivity effectively ( Satthawong et al, 2013 ; Zhai et al, 2016 ; Choi et al, 2017b ; Liu et al, 2018b ). Choi et al (2017a ) reported Fe-Cu catalysts that are used in the CO 2 hydrogenation process.…”
Section: Co 2 Hydrogenation To Jet Fuelsmentioning
confidence: 99%
“…In addition to alkali metals, the addition of secondary metal could also enhance the production of long-chain hydrocarbons. For instance, cuprum and zinc are commonly used promoters as well, favorable for the reduction of Fe 2 O 3 and the adsorption of CO 2 , which could increase the selectivity for C 5 + hydrocarbons and decrease CH 4 selectivity effectively ( Satthawong et al, 2013 ; Zhai et al, 2016 ; Choi et al, 2017b ; Liu et al, 2018b ). Choi et al (2017a ) reported Fe-Cu catalysts that are used in the CO 2 hydrogenation process.…”
Section: Co 2 Hydrogenation To Jet Fuelsmentioning
confidence: 99%
“…[21] Katalysatoren auf Eisenbasis sind fürd ie Herstellung linearer Alkane und auch fürd ie Herstellung von Alkenen und Oxygenaten geeignet. [18,22] Außer dem Katalysator selbst haben auch die Beschaffenheit des Katalysatorträgers, [23,24] der Promotortyp, [25,26] der Reaktortyp [27] und die Arbeitsbedingungen [28] einen wesentlichen Einfluss auf die katalytische Aktivitätu nd die Produktselektivität. [11] Die WGS-Reaktion (CO + H 2 O!CO 2 + H 2 )ist ein in der chemischen Industrie unentbehrliches Verfahren fürd ie Wasserstoffproduktion und zum Beseitigen von Kohlenmonoxid.…”
Section: Katalytische Co-umwandlung:fischer-tropsch-synthese (Fts) Ununclassified
“…Zinc helps to increase the activity of these catalysts in the Fischer–Tropsch process [ 24 , 25 ], increases the adsorption of carbon dioxide [ 24 , 26 , 27 ] and hydrogen [ 27 , 28 ], and increases the activity in the reverse water shift reaction [ 29 , 30 ]. It has been shown that zinc increases the dispersity of iron particles and acts as a structural promoter [ 31 , 32 , 33 , 34 , 35 , 36 ]. Recently, it has been suggested that the addition of zinc is not only a structural promoter, but also increases the stability of the iron-containing catalyst owing to electron density transfer from zinc to iron, promotes the formation of iron carbides, and suppresses the formation of magnetite Fe 3 O 4 during the operation of the iron–zinc coprecipitated catalyst [ 21 ].…”
Section: Introductionmentioning
confidence: 99%